The Quantitative CT assessment in predicting mortality in patients with Combined Pulmonary Fibrosis and Emphysema and Idiopathic Pulmonary Fibrosis: Quantitative CT in combined pulmonary fibrosis and emphysema - Üçsular, Fatma; Karadeniz, Gülistan; Polat, Gülru; Yalnız, Enver; Ayrancı, Aysu; Çinkooğlu, Akin; Savaş, Recep; Solmaz, Hatice; Güldaval, Filiz; Büyükşirin, Melih (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2021)
Aim: We aimed to evaluate the quantitative CT analysis of patients with CPFE in comparison with IPF and emphysema. Methods: Patients with CPFE(n:36), IPF(n:38) and emphysema(n:32) were retrospectively included in the study with the approval of the ethics committee. Results: There was a positive correlation between total lung volume and FVC%, TLCO% and 6 MWT, and negative correlation between mMRC and mortality. Negative correlation was found between right, left lung density and FVC%, TLCO% and 6 MWT, and positive correlation between mortality. Also, total lung volume, right and left lung densities were significant in predicting mortality and cut-off values ​​are ≤3831,> -778 and> -775, respectively(p = 0.040, 0.020, 0.013). Conclusion: Quantitative CT are guiding in predicting mortality of the disease.